2020
DOI: 10.1109/jtehm.2019.2963189
|View full text |Cite
|
Sign up to set email alerts
|

A High-Intensity Exercise Intervention Improves Older Women Lumbar Spine and Distal Tibia Bone Microstructure and Function: A 20-Week Randomized Controlled Trial

Abstract: Introduction: The effects of ageing on bone can be mitigated with different types of physical training, such as power training. However, stimuli that combine increasing external and internal loads concomitantly may improve bone quality. The goal of this study was to assess the efficacy of a combined power and plyometric training on lumbar spine and distal tibia microstructure and function. Methods: 38 sedentary elderly women between 60 and 70 years were randomly allocated in experimental (N = 21) and control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 65 publications
0
34
0
Order By: Relevance
“…However, one study investigating the effect of a 20-week power/plyometric training protocol among elderly women found similar significant changes in lumbar spine TBS and tibia trabecular thickness, while cortical bone remains unchanged. 27 Despite the significant effects on TBS of the lumbar spine, HIT did not improve BMD compared to standard care. It has previously been shown that 6 months of isolated strength training on the lumbar spine may reverse vertebral osteoporosis in LTx recipients.…”
Section: Discussionmentioning
confidence: 89%
“…However, one study investigating the effect of a 20-week power/plyometric training protocol among elderly women found similar significant changes in lumbar spine TBS and tibia trabecular thickness, while cortical bone remains unchanged. 27 Despite the significant effects on TBS of the lumbar spine, HIT did not improve BMD compared to standard care. It has previously been shown that 6 months of isolated strength training on the lumbar spine may reverse vertebral osteoporosis in LTx recipients.…”
Section: Discussionmentioning
confidence: 89%
“…(37,38,(44)(45)(46)(47)(48)68) The five studies in adults only recruited women. (49)(50)(51)69,70) Eight studies were in postmenopausal women (52)(53)(54)(71)(72)(73)(74)(75) and two were in older men. (55,76) Results were combined for older men and women in one study, (77) for peri-and postmenopausal women in another, (78) and for pre-and postmenopausal women in another.…”
Section: Resultsmentioning
confidence: 99%
“…Missing data were obtained by contacting the authors via email a minimum of two times over a 4-week period. The authors of 16 studies were contacted, (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) and five were able to supply the requested information. (44)(45)(46)(47)(48)54) If data were still unavailable but absolute mean changes were provided, we converted these values into percentage mean change by dividing the absolute mean change by baseline mean values and multiplying by 100.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was also an emphasis on the lack of existing information in the high-intensity category and the requirement for more trials to determine the importance of this intervention [ 26 ]. A trial with high-intensity impact exercises with progressive external loading, and strength training with increased internal loading for 20 weeks showed significant improvement in the LS-trabecular bone score, pointing towards improved bone microstructure that is more resistant to fractures [ 23 ]. The high impact and muscle compression force produced from high-intensity/impact exercises may slow down the process of bone aging and contribute to better functional capacity in postmenopausal women [ 23 ].…”
Section: Reviewmentioning
confidence: 99%